The Role of Economic Infrastructure in Regional Development: Strategy to Strengthen Tourism Economic Zones Supporting System - Pangky Tri Febriansyah; Hari Susanto; Mahmud Thoha; Mochammad Nadjib; Firmansyah Firmansyah; Latif Adam; Zamroni Salim; Bintang Dwitya Cahyono; Kanetasya Sabilla (Journal of Indonesian Social Sciences and Humanities, 2018)
Regional based development is an important issue to Indonesia as an archipelago country. One of the alternative to this issue is tourism development, theoretically tourism-dependent economy expectedly has positive impact to the economy. Regional development based on tourism expectedly can be more progressive if supported by tourism special economic zones. Therefore, the availability and appropriateness of the infrastructure must be examined. The aim of this research is to map tourism infrastructure condition in Indonesia, identify the obstacles of tourism infrastructure development, and analyze supporting infrastructure for inclusive and competitive tourism economic zones. The results show that there are still different definitions for tourism that affects the policy implementation. Moreover, there is still gap between infrastructure availability and needs in the tourism development, especially in tourism economic zones. Otherwise, community in the tourism economic zones surrounding areas have relatively strong social capital to support tourism. This condition should be the other supporting factors besides proper infrastructure and governance.